PENGUATAN STRATEGI PEMBELAJARAN MUHASABAH AN NAFS UNTUK MENGENALI POTENSI DIRI SISWA PADA MATA PELAJARAN AKIDAH AKHLAK DI MA MIFTAHUL QULUB POLAGAN GALIS PAMEKASAN - Syaifurrahman Nabawi; Muliatul Maghfiroh (STKIP Subang, 2026)
This study examines the strengthening of muhasabah an-nafs learning strategies in helping students recognize their self-potential in the Aqidah Akhlak subject at MA Miftahul Qulub Polagan Galis Pamekasan. The study is grounded in the issue of students’ low reflective awareness of their abilities and personal character, highlighting the need for a learning approach that emphasizes value internalization and self-evaluation. The objective of this research is to describe the implementation, effectiveness, and impact of the muhasabah an-nafs strategy on students’ self-potential recognition. This study employs a qualitative approach with a case study design, utilizing observation, in-depth interviews, and documentation techniques. The findings indicate that strengthening the muhasabah an-nafs strategy enhances students’ self-awareness, reflective honesty, and intrinsic motivation in developing both academic and spiritual potential. Furthermore, this strategy contributes to fostering religious character and personal responsibility. The study offers a contribution in the form of a reflective, spiritually grounded learning model that is contextually relevant for improving the quality of Aqidah Akhlak education.